Influence of temperate, subtropical, and tropical fruit consumption on risk of type 2 diabetes in an Asian population. Issue 3 (8th February 2017) - Alperet, Derrick Johnston; Butler, Lesley M; Koh, Woon-Puay; Yuan, Jian-Min; van Dam, Rob M
ABSTRACT: Background: Findings on the relation between fruit consumption and the risk of type 2 diabetes mellitus (T2DM) have been inconsistent. Objectives: We examined whether the consumption of total, temperate, subtropical, and tropical fruit is associated with T2DM risk and whether differences in the carbohydrate quality of fruit influence T2DM risk in Asians. Design: We included 45, 411 participants in the Singapore Chinese Health Study who were 45–74 y old and had no diabetes, cancer, or cardiovascular disease at recruitment (1993–1998). Fruit intake was assessed with the use of a validated food-frequency questionnaire. Physician-diagnosed incident T2DM cases were reported at follow-up 1 (1999–2004) and follow-up 2 (2006–2010) interviews. Cox proportional hazards regression was used to estimate HRs and 95% CIs of diabetes risk. Results: In 494, 741 person-years of follow-up, 5207 participants developed T2DM. After adjustment for lifestyle and dietary risk factors, high total fruit consumption was not consistently associated with lower T2DM risk [men: HR of 1.33 (95% CI: 1.04, 1.71) for ≥3 servings/d compared with <1 serving/wk ( P -trend = 0.17); women: HR of 0.88 (95% CI: 0.71, 1.11) ( P -trend = 0.008); P -interaction = 0.003]. The direct association in men was observed for higher–glycemic index (GI) fruit [HR: 1.51 (95% CI: 1.22, 1.86) for ≥1 serving/d compared with rarely consumed; P -trend = 0.001] but not for lower or moderate GI fruit. In women, the consumption of temperate fruit, but not of subtropical or tropical fruit, was associated with lower T2DM risk [HR: 0.79 (95% CI: 0.67, 0.92) for ≥1 serving/d compared with rarely; P -trend = 0.006]. Conclusions: The consumption of temperate fruit, such as apples, was associated with a lower risk of T2DM in women, whereas the consumption of higher-GI fruit, such as bananas, was associated with higher risk in men. The impact of fruit consumption on the risk of diabetes may differ by the type of fruit, which may reflect differences in the glycemic impact or phytochemical content.